Outcomes of small for gestational age micropremies depending on how young or how small they are - Hee Joon Yu; Eun Sun Kim; Jin Kyu Kim; Hye Soo Yoo; So Yoon Ahn; Yun Sil Chang; Won Soon Park (Korean Pediatric Society, 2011)
PurposeThe outcomes of small for gestational age (SGA) infants especially in extremely low birth weight infants (ELBWIs) are controversial. This study evaluated the mortality and morbidity of ELBWIs, focusing on whether or not they were also SGA.MethodsThe medical records of 415 ELBWIs (birth weight <1,000 g), who were inborn and admitted to the Samsung Medical Center neonatal intensive care unit from January 2000 to December 2008, were reviewed retrospectively. Mortality and morbidities were compared by body size groups: very SGA (VSGA), birth weight ≤3rd percentile; SGA, 3rd to 10th percentile; and appropriate for gestational age (AGA) infants, >10th percentile for gestational age. For gestational subgroup analysis, groups were divided into infants with gestational age ≤24+6 weeks (subgroup I), 25+0 to 26+6 weeks (subgroup II), and ≥27+0 weeks (subgroup III).ResultsGestational age was 29+2±2+6 weeks in the VSGA infants (n=49), 27+5±2+2 weeks in the SGA infants (n=45), and 25+4±1+4 weeks in AGA infants (n=321). Birth weight was 692±186.6 g, 768±132.9 g, and 780±142.5 g in the VSGA, SGA, and AGA groups, respectively. Cesarean section rate and maternal pregnancy-induced hypertension were more common in the VSGA and SGA than in AGA pregnancies. However, chorioamnionitis was more common in the AGA group. The mortalities of the lowest gestational group (subgroup I), and also of the lower gestational group (subgroup I+II) were significantly higher in the VSGA group than the SGA or AGA groups (P=0.020 and P=0.012, respectively). VSGA and SGA infants showed lower incidence in respiratory distress syndrome, ductal ligation, bronchopulmonary dysplasia, intraventricular hemorrhage than AGA group did. However, by multiple logistic regression analysis of each gestational subgroup, the differences were not significant.ConclusionOf ELBWIs, extremely SGA in the lower gestational subgroups, had an impact on mortality, which may provide information useful for prenatal counseling.